Deadly force: Contract, killing, sacrifice. (August 2019) - Bradley, Arthur
This article proposes a political prehistory of drone theory that traces its juridico-political evolution from the 17th century to the present day. To outline my argument, I construct a constellation between Hobbes's theory of sovereign punishment in Leviathan and Chamayou's critique of drone warfare in Drone Theory to illuminate the political origins of drone violence. First, I argue that Hobbes's social contract theory lays the conceptual groundwork for Chamayou's drone theory. Second, I contend that Hobbes's theory of the sovereign punishment of domestic citizens preempts Chamayou's critique of drone warfare against foreign enemies. Finally, I speculate that Hobbes's theory of punishment is founded upon a sacrificial paradigm that returns in the phenomenon of domestic drone strikes. In summary, I argue that Hobbes might be something close to the first drone theorist insofar as his political theory systematically produces the state of exception between citizen and enemy in which the drone operates today. What, then, are the theoretical origins of drone warfare? How does the punishment of citizens prefigure drone warfare against foreign enemies? To what extent might even citizens themselves be a species of drone who may be activated by the sovereign at any point?